Association or Causation? Exploring the Oral Microbiome and Cancer Links. (December 2020) - Teles, F.R.F.; Alawi, F.; Castilho, R.M.; Wang, Y.
Several epidemiological investigations have found associations between poor oral health and different types of cancer, including colorectal, lung, pancreatic, and oral malignancies. The oral health parameters underlying these relationships include deficient oral hygiene, gingival bleeding, and bone and tooth loss. These parameters are related to periodontal diseases, which are directly and indirectly mediated by oral bacteria. Given the increased accessibility of microbial sequencing platforms, many recent studies have investigated the link between the oral microbiome and these cancers. Overall, it seems that oral dysbiotic states can contribute to tumorigenesis in the oral cavity as well as in distant body sites. Further, it appears that certain oral bacterial species can contribute to carcinogenesis, in particular, Fusobacterium nucleatum and Porphyromonas gingivalis, based on results from epidemiological as well as mechanistic studies. Yet, the strength of the findings from these investigations is hampered by the heterogeneity of the methods used to measure oral diseases, the treatment of confounding factors, the study design, the platforms employed for microbial analysis, and types of samples analyzed. Despite these limitations, there is an overall indication that the presence of oral dysbiosis that leads to oral diseases may directly and/or indirectly contribute to carcinogenesis. Proper methodological standardized approaches should be implemented in future epidemiological studies as well as in the mechanistic investigations carried out to explore these results.